2023
DOI: 10.1186/s12889-023-16369-1
|View full text |Cite
|
Sign up to set email alerts
|

Educational inequality in multimorbidity: causality and causal pathways. A mendelian randomisation study in UK Biobank

Teri-Louise North,
Sean Harrison,
Deborah C Bishop
et al.

Abstract: Background Multimorbidity, typically defined as having two or more long-term health conditions, is associated with reduced wellbeing and life expectancy. Understanding the determinants of multimorbidity, including whether they are causal, may help with the design and prioritisation of prevention interventions. This study seeks to assess the causality of education, BMI, smoking and alcohol as determinants of multimorbidity, and the degree to which BMI, smoking and alcohol mediate differences in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This underscores the significance of addressing and reducing social inequalities in health and identifying groups that require special attention from public health services. For instance, a recent study conducted in the United Kingdom, which analysed various determinants of multimorbidity, indicated that the elevated risk of multimorbidity among lower-educated individuals could be partially attributed to their higher BMI and increased smoking rates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the significance of addressing and reducing social inequalities in health and identifying groups that require special attention from public health services. For instance, a recent study conducted in the United Kingdom, which analysed various determinants of multimorbidity, indicated that the elevated risk of multimorbidity among lower-educated individuals could be partially attributed to their higher BMI and increased smoking rates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%